Correlation of Indeterminate Lesions of COVID-19 Pneumonia Detected on Computed Tomography with RT-PCR Results - Aydin, Nevin; Cihan, Çağatay; Us, Tercan; Öz, Yasemin; Öztunalı, Çiğdem; Yılmaz, Şenay; Alataş, Füsun; Erginel, Sinan; Kurt, Emel; Ak, Güntülü; Yıldırım, Hüseyin (Current Medical Imaging, 2022)
Background: The typical findings of COVID-19 pneumonia include multilobar groundglass opacities and consolidation areas observed predominantly in the basal and peripheral parts of both lungs in computed tomography. Objective: The current study aimed to correlate indeterminate lesions of COVID-19 pneumonia detected on computed tomography with the results of the reverse transcription-polymerase chain reaction (RT-PCR) test. Methods: Patients with high-resolution computed tomography images that were reported to contain indeterminate lesions in terms of COVID-19 pneumonia were included retrospectively in the study. The lesions were categorized and the patterns were classified. The RT-PCR-positive and the RTPCR- negative patients were compared. P<0.05 was accepted as the statistical significance limit. Results: The RT-PCR-positive patients exhibited a higher rate of peripheral lesions. Limited consolidation areas were not detected in the RT-PCR-positive patients. In the RT-PCR-negative patients, the rates of acinar nodules and the tree-in-bud pattern were significantly higher. The RTPCR- negative patients had higher nodular contour features and lesion coalescence. In the subgroup consisting of lesions with ground-glass opacities and/or ground-glass opacity around the nodule, the rate of nodular contour positivity was significantly higher in the RT-PCR- positive patients. Conclusion: COVID-19 pneumonia should be suspected when peripheral indeterminate lesions are detected. When indeterminate lesions, such as tree-in-bud pattern, acinar nodules and limited consolidation area are detected, alternative diagnoses should be considered first, even if there are ground glass opacities accompanying these lesions.
Keywords: COVID-19 pneumonia